Masatua sebagai Salah Satu Kearifan Lokal Bali Untuk Melestarikan Bahasa Bali - I Dewa Agung Made Candrakusuma (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
Masatua tradition means activities to tell satua or storytelling. The only things that were conveyed were the satua-satua that used Balinese. Satua Bali is one of the traditional Balinese art products that are given to children, but unfortunately the existence of the application of Balinese satua is currently very minimal even though Satua Bali is an ancestral heritage that should be preserved and preserved considering the moral values contained in this Balinese satua are very both in the formation of children's character and can also instill a sense of respect for children towards local culture and customs. However, life before was different from now. In this modern era, the Balinese masatua tradition has begun to fade and is certain to become a past story. Satua Bali, which used to be read by parents before the children go to bed, is different from the present condition, where the parents are so busy with their work that the masatua culture is slowly starting to be abandoned. Satua which is an oral literature that has become the culture of the Balinese people, especially what is called speech literature, which is the forerunner to the development and birth of literary life. In this research, there are three problems studied, namely: (1) How is the Masatua tradition both formally and informally; and (2) The use of sor singgih in the Mesatua tradition. So based on the analysis that has been done, it can be seen and concluded that: (1) the masatua tradition is usually carried out before the child goes to sleep which occurs in the family circle. Masatua in non-formal activities, in this case in the family, is a traditional cultural activity. In formal activities, this masatua activity has occurred which has been packaged in learning activities. (2) The use of Balinese is closely related to the Masatua tradition, both formally and informally. It is very important to choose the vocabulary or level of the Balinese language so that it is used correctly and can be understood by listeners, namely the child in the family or students and even the general public.